Spatio-temporal change in species and morphological diversity of reef fishes in the South Pacific Ocean : a thesis presented in partial fulfilment of the requirements for the degree of Master of Biological Sciences at Massey University, New Zealand - Kilduff, Liam (Massey University, 2020)
The geography of the South Pacific, with its numerous oceanic islands, offers a unique opportunity to examine prevailing theories on the accumulation and maintenance of biodiversity. It is well recognised that for most taxonomic groups, species richness declines poleward from the equator and eastward across the South Pacific. However, as ocean temperatures warm and oceanographic barriers move with climate change, shifts in the ranges of tropical species towards higher latitudes may lead to changes in community structure and resilience in subtropical locations. Here, I examine the existing biodiversity gradients of reef fishes across the South Pacific Ocean, and identify potentially climate-induced temporal shifts of tropical species into the high latitude and isolated Rangitāhua archipelago. Furthermore, I examine morphological changes across latitude and longitude to identify traits associated with species colonisation ability and function within the often species depauperate communities in more isolated and southerly regions of the South Pacific. Additionally, I examine how morphological changes over time might impact the morphological space of the fish community at Rangitāhua. I assessed morphological change in 12 standard measurements for 948 fish species, from nine families found on the reefs surrounding 19 of the major island groups of the South Pacific Ocean. I found that while species richness followed the predicted decline towards the east and south, morphological diversity showed the opposite trend, increasing east and south. Furthermore, similar morphological changes were evident with body size and pre-orbit length increasing in response to both latitude and longitude, although more significantly with longitude. Despite this, analysis of individual families revealed unique patterns of morphological change within the South Pacific Ocean, may be indicative of the differing strategies of each family to colonise and persist in more southerly and easterly locations. Within Rangitāhua, using a list of 149 shallow Teleost fishes including the dates of their first sighting, I identified a temporal shift in the biogeographic affinities of the fish assemblage with an increasing contribution from tropical regions over time. Newly discovered, more tropical species, only occurred in low numbers, possibly because they are still in the early colonising stage or because the islands environment is still more temperate than these fish require to increase in abundance significantly. Despite also finding that the morphological diversity of the fish assemblage changed through time, morphological change was not directional, indicating that although new species are arriving, their morphology is similar to longer-established, more temperate fishes. Therefore, although the frequency of species with tropical biogeographic affinities is increasing over time at Rangitāhua, this is not strongly impacting the community’s morphological variation. My results for Rangitāhua support the global pattern of tropical species re-distributing towards higher latitude region over time. Overall, my thesis examining both species and morphological change in reef fishes across large-scale geographic gradients within the South Pacific Ocean provides insight into potential future biodiversity changes and may allow us to predict which species are likely, or capable of extending their ranges towards the poles.
Keywords: 310907 Animal physiological ecology